Phytoplankton communities in two wide-open bays in the Iberian upwelling system - Santos, Mariana (2021)
The main meteorological and oceanographic drivers shaping phytoplankton community structure and dynamics are investigated in two wide-open bays influenced by coastal upwelling. Local processes influencing the proliferation of harmful algal bloom species were also investigated. The work was developed during one year in Lisbon Bay (central-west coast) and in Lagos Bay (south coast), both located on the upwelling shadow of prominent headlands. In both bays, the results indicated a bi-modal annual pattern in phytoplankton biomass, and phytoplankton concentration maxima, between spring and late-summer, were associated with high diatom abundances. In Lagos Bay, higher dinoflagellate abundances were observed from spring to autumn, while in Lisbon Bay these were recorded from late-summer to autumn. The coccolithophores were a frequent group all year round in Lisbon Bay, which contrasts with Lagos Bay where they were the least frequent group. The phytoplankton community structure showed significant spatial and seasonal differences. The community succession pattern indicated the existence of four biological seasons in Lisbon Bay and at the offshore site in Lagos Bay. By contrast, the nearshore site in Lagos Bay was characterized by having no significant differences between summer and autumn. Differences in HAB species/groups were also observed between the bays. In general, HABs occurred at higher concentrations and were more persistent in Lagos Bay. In both bays, winter assemblages were influenced by water column mixing processes, although precipitation was also relevant in Lagos. Upwelling was a key driver of the spring phytoplankton community in Lagos Bay, while in Lisbon Bay other factors seemed to drive the spring phytoplankton assemblages. Both summer and autumn communities were related to thermal stratification. In autumn, the occurrence of reversal circulation patterns also played an important role in shaping the phytoplankton communities, especially in Lagos Bay. Overall, this study revealed differences on phytoplankton community patterns in two wide-open bays, shaped by the local environmental variables.